Cooperative preferences fluctuate across the menstrual cycle - Christine Anderl; Tim Hahn; Karolien Notebaert; Claudia Klotz; Barbara Rutter; Sabine Windmann (Judgment and Decision Making, 2015)
Social Value Orientation (SVO) refers to an individual's preference for the division of resources between the self and another person. Since evidence suggests that hormones influence several facets of human social behavior, we asked whether SVO might fluctuate across the female menstrual cycle. Using self-report data obtained in two independent online studies, we show that cooperative preferences, as indexed by SVO, are indeed significantly more prosocial in the early follicular compared to the midluteal phase in naturally ovulating women. Furthermore, when estimating hormonal variations from norm data, we found estradiol, but not progesterone or testosterone, to be a significant predictor of SVO across the menstrual cycle in both studies, with a negative correlation. Our findings provide evidence that the willingness to cooperate varies across the natural female menstrual cycle and highlight the potential of investigating psychological effects of ovarian sex hormones.